Dyshidrosiform pemphigoid with Parkinsonism in a nonagenarian Maharashtrian female - Tabassum Behlim; Yugal K Sharma; Nitin D Chaudhari; Kedarnath Dash (Wolters Kluwer Medknow Publications, 2014)
Dyshidrosiform pemphigoid is a rare variant of bullous pemphigoid localized to the hands and feet whose characteristic subepidermal blisters develop as a result of binding of the IgG autoantibodies to intracellular plaque and extracellular face of the hemidesmosome recognizing a 230-kDa plakin molecule (BP230, BPAg1or BPAg1e) and a 180-kDa transmembrane protein. Neurodegenerative processes (viz., stroke, dementia, Parkinsonism, epilepsy, etc) uncover BPAg1-n, an alternatively spliced form of BPAg1-e that stabilizes the cytoskeleton of sensory neurons, generating autoantibodies that may subsequently lead to BP by cross-reacting with BPAg1-e. We present a patient with Parkinsonism who later developed blisters, erosions and crusts localized to the palms and soles, confirmed histopathologically as bullous pemphigoid. To the best of our knowledge, ours is the first case report from India wherein Parkinsonism-generated autoantibodies led to the development of dyshidrosiform pemphigoid due to their cross-reactivity with BPAg1-e.